A mineral extract from red algae ameliorates chronic spontaneous colitis in IL-10 deficient mice in a mouse strain dependent manner. - FALLON, PADRAIC (My University, 2014)
Inflammatory bowel disease is an urgent public health problem with a high incidence in developed countries. Alterations of lifestyle or dietary interventions may attenuate the disease progression and increase the efficacy of current therapies. Here we tested the effect of chronic supplementation with a mineral extract from red marine algae - rich in calcium (34%), magnesium, phosphorus, selenium and other trace minerals - in a clinically relevant model of spontaneous enterocolitis, interleukin (IL)-10(-/-) mice. The mineral extract was administered in the drinking water of Il10(-/-) mice on C57BL/6 J and BALB/c strain backgrounds for 25 weeks commencing from 3 to 4 weeks of age. The mineral extract ameliorated the spontaneous development of colitis and severity of disease in Il10(-/-) mice on a C57BL/6 J background. Mineral extract-treated Il10(-/-) C57BL/6 J strain mice had significantly reduced mortality, circulating levels of serum Amyloid A and reduced colonic tissue damage. In contrast, comparable treatment of Il10(-/-) mice on a BALB/c background with the mineral extract did not alter the course of colitis. These data demonstrate that chronic supplementation with a natural mineral extract selectively ameliorates spontaneous mild-moderate colitis in Il10(-/-) mice on a C57BL/6 J, but does not attenuate more moderate-severe colitis in BALB/c strain animals.
PUBLISHED
Keywords: Lithothamnion spp.; colitis; interleukin-10 deficient mice; mineral extract; Immunology, Inflammation & Infection; Biomedical sciences